TAX PLANNING ATAS PAJAK PENGHASILAN BADAN PADA SEMUA PERSEKUTUAN KOMANDITER (CV) DI KOTA LUBUKLINGGAU DAN KOTA BENGKULU - Dheo Rimbano; Mirra Sri Wahyuni (Universitas Prof. Dr. Hazairin SH, 2018)
Corporate income tax that must be paid. Neither, awareness of paying is poor, Islam is more familiar with the term â€œZakatâ€ than tax (Awareness in paying zakat is â€˜very highâ€™ for Muslims). We know, raising awareness begins with the planning process, so the constraints in every plan to pay taxes need to be known. Possible taxpayers already know of its obligations, but the meaning is like a